Development of a modified C-BARQ for evaluating behavior in working dogs - Hare, Elizabeth; Essler, Jennifer Lynn; Otto, Cynthia M.; Ebbecke, Dana; Serpell, James A. (Frontiers in Veterinary Science, 2024)
Current high demand for effective odor detection dogs calls for the development of reliable methods for measuring performance-related behavioral phenotypes in these highly specialized working animals. The Canine Behavioral Assessment & Research Questionnaire (C-BARQ) is a widely used behavioral assessment tool among working dog organizations with a demonstrated ability to predict success/failure of dogs in training. However, this instrument was developed originally to study the prevalence of behavior problems in the pet dog population, and it therefore lacks the capacity to measure specific behavioral propensities that may also be important predictors of working dog success. The current paper examines the factor structure, internal reliability, and content validity of a modified version of the C-BARQ designed to evaluate four new domains of canine behavior in addition to those encompassed by the original C-BARQ. These domains, labelled Playfulness, Impulsivity, Distractibility and Basophobia (fear of falling), respectively, describe aspects of canine behavior or temperament which are believed to contribute substantially to working dog performance. Exploratory factor analysis of owner/handler questionnaire responses based on a sample of 1117 working odor detection dogs extracted a total of 15 factors, 10 of which correspond to original C-BARQ factors. The remaining 5 comprise the four new domains as well as a fifth new factor labelled Food focus. The resulting Working Dog Canine Behavioral Assessment & Research Questionnaire (WDC-BARQ) successfully expands the measurement capacities of the original C-BARQ to include dimensions of behavior/temperament of particular relevance to many working dog populations.